Distribution of teachers' salaries according to remuneration levels in a public university - Cuadros-Ojeda, Víctor P. (2021)
Introduction. In Peru, according to the University Law Nº 30220, the salaries of the teachers of the universities must be homologated with those of judicial magistrates; however, to date this has not yet been fulfilled. However, it is necessary to point out that after more than 20 years of complaints from university professors, in 2005 the process of homologation was initiated, which has allowed an increase in remunerations; however, there are differences between categories: "auxiliary", "associate" and "main full time", taking into account that they perform the same tasks. Objective. In this context, the objective of this research is to demonstrate the distribution of teachers' salaries according to category and dedication, as well as the presence of inequalities or salary differentiation differentiation at the Universidad Nacional Hermilio Valdizán (UNHEVAL). Methods. The Gini coefficient and the Lorenz curve were used, for the period 2011-2020. Results. It was shown that the Gini coefficient yielded a value of 0.17 and the Lorenz curve is below and very close to the line of perfect equality. Conclusions. It is concluded that there are no significant differences in the salaries of the different categories of teachers at the Universidad Nacional Hermilio Valdizán.